Effects of health expenditures on infant and child mortality rates: A dynamic panel data analysis of 37 African countries - HOUENINVO, GBODJA HILAIRE (My University, 2022)
This paper examines the effect of public and private health spending on health outcomes measured by infant and child mortality rate using a panel of 37 African countries over the period 1995–2018. Based on both system generalized method of moments and least squared dummy variable corrected bias estimators, we find that the level of public health expenditures has statistically significant positive effects on mortality reduction. However, private health spending has a statistically significant positive effect on infant and child mortality rates when it interacts with public health spending. This means that the health effect of private health expenditure is strengthened by public health spending. Conditioning on the level of private health expenditure, the total effect of public health expenditure on child mortality reduction is slightly higher in absolute value than that of private health expenditure. The main policy implication that emerges from our results is the need to increase public health expenditure and support the effectiveness of private health expenditure. This additional fund should be allocated to some specific expenditure categories which have a very direct link with child and infant mortality rates.
Keywords: Africa; dynamic panel model; health expenditures; health outcomes